2021
DOI: 10.1002/cpdd.899
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Tofacitinib in Patients With Moderate to Severe Ulcerative Colitis

Abstract: Tofacitinib is an oral, small molecule Janus kinase inhibitor for the treatment of ulcerative colitis (UC). We characterized tofacitinib pharmacokinetics in patients with moderate to severe UC, and the effects of covariates on variability in pharmacokinetic parameter estimates. Data were pooled from 1 8‐week phase 2 and 2 8‐week phase 3 induction studies, and a 52‐week phase 3 maintenance study (N = 1096). Population pharmacokinetic analysis was conducted using nonlinear mixed‐effects modeling. Potential predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 32 publications
3
10
0
Order By: Relevance
“…Use of C avg as the predictor is consistent with E‐R model predictions for tofacitinib in rheumatoid arthritis 15 . Plasma concentrations of tofacitinib have been shown to be stable long‐term in patients with UC, providing there is no change in dose 11 . In contrast, biologic therapies can be susceptible to clearance mechanisms that result in low drug exposure and subsequent loss of response in some patients 12 .…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Use of C avg as the predictor is consistent with E‐R model predictions for tofacitinib in rheumatoid arthritis 15 . Plasma concentrations of tofacitinib have been shown to be stable long‐term in patients with UC, providing there is no change in dose 11 . In contrast, biologic therapies can be susceptible to clearance mechanisms that result in low drug exposure and subsequent loss of response in some patients 12 .…”
Section: Discussionsupporting
confidence: 57%
“…The geometric mean C avg at 10 mg b.i.d. (33.6 ng/mL; derived from previously reported PK parameters) 11 corresponded to ED 67 on the E‐R curve for remission.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…A study on tofacitinib’s pharmacokinetics showed that no significant change in tofacitinib exposure (apparent oral clearance) was seen over the duration of treatment. Additionally, age, sex, body weight, and baseline disease severity had no clinically significant impact on the apparent oral clearance and volume of distribution, indicating no need to adjust the dose of tofacitinib [ 62 ].…”
Section: Resultsmentioning
confidence: 99%